ESOPHAGEAL CARCINOMA: IS SQUAMOUS CELL CARCINOMA DIFFERENT DISEASE COMPARED TO ADENOCARCINOMA? A transversal study in a quaternary high volume hospital in Brazil - TUSTUMI,Francisco (2016)
ABSTRACT Background Esophageal cancer is one of the leading causes of mortality among the neoplasms that affect the gastrointestinal tract. There are several factors that contribute for development of an epidemiological esophageal cancer profile in a population. Objective This study aims to describe both clinically and epidemiologically the population of patients with diagnosis of esophageal cancer treated in a quaternary attention institute for cancer from January, 2009 to December, 2011, in Sao Paulo, Brazil. Methods The charts of all patients diagnosed with esophageal cancer from January, 2009, to December, 2011, in a Sao Paulo (Brazil) quaternary oncology institute were retrospectively reviewed. Results Squamous cell cancer made up to 80% of the cases of esophageal cancer. Average age at diagnosis was 60.66 years old for esophageal adenocarcinoma and 62 for squamous cell cancer, average time from the beginning of symptoms to the diagnosis was 3.52 months for esophageal adenocarcinoma and 4.2 months for squamous cell cancer. Average time for initiating treatment when esophageal cancer is diagnosed was 4 months for esophageal adenocarcinoma and 4.42 months for squamous cell cancer. There was a clear association between squamous cell cancer and head and neck cancers, as well as certain habits, such as smoking and alcoholism, while adenocarcinoma cancer showed more association with gastric cancer and gastroesophageal reflux disease. Tumoral bleeding and pneumonia were the main causes of death. No difference in survival rate was noted between the two groups. Conclusion Adenocarcinoma and squamous cell carcinoma are different diseases, but both are diagnosed in advanced stages in Brazil, compromising the patients' possibilities of cure.